Principals Administrative Strategies and Academic Performance of Public Secondary Schools in Mount Elgon Sub County, Bungoma County, Kenya - , Maximilla Wakoli; Kisilu Kitainge (Prof), (IJRDO- Journal of Educational Research, 2019)
The principal’s main role is to promote academic performance. This role can only be executed with the required administrative strategies hence the need for principals to have sound administrative strategies that ensure a good leadership model. The purpose of the study was to investigate principals’ administrative strategies and influence student performance in Mount Elgon Sub County Secondary schools. The study was guided by the Max Weber theory on division of labour. The study population comprised of 72 principals and 1,280 teachers serving 72 secondary schools within the Sub County. The data was collected through questionnaire administered to teachers and principals. The study found out that performance of public secondary schools in the sub county had been below average for the past five years (2014-2018). Further, the study discovered that the application of various administrative strategies influenced performance of schools. Institutions that used participative strategies performed better in academic performance than those that used non-participative strategies. The study recommends that training needs to be provided to principals on management and leadership styles that are critical for performance improvement in their schools. In addition, teachers need to be continuously involved in decision making in schools